Posttreatment Changes of the Elbow - Grieser, Thomas (Seminars in Musculoskeletal Radiology, 2022)
Radiologists should be familiar with the typical surgical procedures applied at the elbow and aware of the spectrum of normal and pathologic appearances of posttreatment situations throughout all radiologic modalities. Most important in the case of posttraumatic surgical elbow procedures is correct postoperative elbow joint alignment, appropriate fixation of joint-forming fragments, and proper insertion of screws, plates, and anchor devices that do not conflict with intra-articular or bony structures. To report soft tissue repair procedures correctly, radiologists need to know the broad spectrum of different techniques applied and their appearance on magnetic resonance imaging.
Keywords: elbow osteosynthesis; elbow prosthesis; postoperative complications; fracture malunion; posttraumatic hyperostosis